(untitled) (Eurasian Journal of Ecology, 2024)
The main sources of environmental pollution are located in cities. Therefore, the study of urban ecosystems is an important issue. During the study, we studied the development of the cities of Imishli, Saatli and Sabirabad, located on the banks of the Araz River, and their impact on the environment. This time we opted for modern methods. Satellite images of the study area were downloaded and processed. Landsat 5, 8 and 9 satellite images were processed, vegetation, water basin and other components of the study area were analyzed. It is determined that the environment in the study area has changed a lot. Key words: urban ecosystem, Landsat satellite, ecological situation, Araz river